2014
DOI: 10.1055/s-0034-1376202
|View full text |Cite
|
Sign up to set email alerts
|

Reference Range of Cerebrospinal Fluid Opening Pressure in Children: Historical Overview and Current Data

Abstract: The lumbar puncture and cerebrospinal fluid (CSF) opening pressure (OP) in children remains an essential diagnostic test for children with suspected elevated intracranial pressure. Recent prospective data have revised the normative CSF OP values and described how clinical variables such as age, depth of sedation, and obesity may influence the measurements. In addition, the new normative data are now reflected in revised diagnostic criteria for idiopathic intracranial hypertension/pseudotumor cerebri syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 19 publications
3
33
0
Order By: Relevance
“…In another retrospective observational study, the highest opening pressure in pediatric IIH was between 20 and 24 cmH 2 O in 11% of the patients while it was between 25 and 39 cmH 2 O in 48% and more than 40 cmH 2 O in 42% of the patients [16]. In a newer study, opening pressure ≥ 28 cmH 2 O is mandatory for diagnosis of intracranial hypertension for obese patients and 25 cmH 2 O if the patient is not obese [13].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In another retrospective observational study, the highest opening pressure in pediatric IIH was between 20 and 24 cmH 2 O in 11% of the patients while it was between 25 and 39 cmH 2 O in 48% and more than 40 cmH 2 O in 42% of the patients [16]. In a newer study, opening pressure ≥ 28 cmH 2 O is mandatory for diagnosis of intracranial hypertension for obese patients and 25 cmH 2 O if the patient is not obese [13].…”
Section: Discussionmentioning
confidence: 93%
“…The clinical presentation of IIH is variable and the diagnostic criteria have changed over time, but currently, Dandy criteria and its modifications which involve symptoms and signs of increased intracranial pressure with elevated CSF pressure without laboratory or radiological evidence of intracranial lesion, infection, or hydrocephalus are used for diagnosis of IIH in adult patients [2,4,5,12]; however, there is no agreement for specific diagnostic criteria in pediatric IIH due to controversies about the diagnostic value of CSF opening pressure [13][14][15][16], in addition to the difference in the presentation and clinical finding between children and adolescent patients [2,16].…”
Section: Introductionmentioning
confidence: 99%
“…Avery, et al suggested that the reference range for CSF opening pressure in children should be reconsidered, based on a study of cerebrospinal fluid opening pressure in 472 healthy children between the ages of 1 and 18 years that determined the CSF opening pressure 90th percentile in the healthy study population was 28 cm of water [43]. In our present qMRI study, CSF opening pressure rose above 20 cm and progressed well above 28 cm in all infantile patients for whom sequential measurements were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…analyzed the OP of 197 children and found a mean OP of 19.6 cm H 2 023. Furthermore, given the 10 th /90 th percentage of Avery’s data was 11.5 and 28 cm H 2 O, it has been suggested that an abnormal OP should be consider that of >28 cm H 2 O2324. Six of 25 MPS-IH patients had OP greater than 30 cm H 2 O.…”
Section: Discussionmentioning
confidence: 99%